Net Returns from Segregating Dark Northern Spring Wheat by Protein Concentration during Harvest. (1st July 2016) - Long, Dan S.; McCallum, John D.; Martin, Charles T.; Capalbo, Susan
Abstract : In‐line, optical sensing has been developed for on‐combine measurement and mapping of grain protein concentration (GPC). The objective of this study was to estimate changes in costs and net returns from using this technology for segregation of the dark northern spring (DNS) subclass of hard red wheat ( Triticum aestivum L.) by GPC. Site‐specific GPC and yield data were obtained from 21 DNS wheat fields in northern Montana over 11 yr (1994–2004). Several hundred measurements of GPC were obtained within each field by means of whole grain spectroscopy. A calculator was built to predict the best economic point at which to segregate grain into two bins and define the protein level and quantity of each volume of grain. Partial budget analysis was used to estimate net returns and determine if segregating wheat was more profitable than bulking wheat in one bin. Segregation consistently increased the value of each megagram of grain if the GPC of a field was below the upper limit of a price schedule and also did not coincide with a price step. Added income was insufficient to offset costs of segregation based on 21‐yr (1994–2014) average market prices. Costs could be offset in years when prices were sharply higher than average 21‐yr prices. These results suggest that grain segregation may be profitable under certain conditions. Further refinements to the technique are needed to reduce equipment costs and benefit the producer. Core Ideas New optical sensors are potentially useful for segregating grain by protein content during harvest. Segregating grain may increase profitability if added income exceeds added costs. Profits are possible under the right circumstances.